A Socio-Economic Portrait of Foreign Students in Poland - as Exemplified by Students from Former CIS Studying at WSB University in Wroclaw = Socjoekonomiczny portret studentów obcokrajowców w Polsce - przykład studentów z państw dawnej WNP studiujących w WSB we Wrocławiu - Majkut, Robert; Pluta, Jacek; Rybczyński, Radosław (Zielona Góra: Faculty of Economics and Management Press)
A noticeably increased intensity of migration becomes a very important issue with regard to economic, socio-cultural and political matters. Broader flow of people results in the occurrence of numerous threats, but also provides opportunities and benefits for both the participants of migration flows, and the areas to which the flowis directed.
Keywords: migracje; asymilacja; aktywność ekonomiczna imigrantów; studenci obcokrajowcy; WSB (Wyższa Szkoła Bankowa) (Wrocław); migrations; assimilation; economic activity of immigrants; foreign students; WSB University in Wroclaw